Penggunaan Model Problem Based Learning (PBL) Berbantuan Media Video Untuk Meningkatkan Proses Pembelajaran di Kelas IV SDN 39 Pasar Gompong Pesisir Selatan: Penggunaan Model Problem Based Learning (PBL) Berbantuan Media Video Untuk Meningkatkan Proses Pembelajaran di Kelas IV SDN 39 Pasar Gompong Pesisir Selatan - Apfani, Sry (LP2M Universitas Adzkia, 2023)
This writing is motivated by educators in the integrated thematic learning process that has not been fully implemented. The purpose of this paper is to describe the improvement of the thematic integrated learning process using the Problem based learning (PBL) model assisted by video media at SDN 39 Pasar Gompong, Pesisir Selatan Regency.This type of writing is Class Action Writing (CAR), using qualitative and quantitative approaches. The subjects of this writing are writers (practitioners), educators (observers) and fourth grade students at SDN 39 Pasar Gompong, Pesisir Selatan Regency, totaling 16 people. The results of the writing show an increase in the integrated thematic learning process in grade IV. This increase can be seen from: the learning implementation plan (RPP) in the first cycle of the first meeting was 62.5%, in the first cycle of the second meeting it was 67.5% and in the second cycle it was 75%. The implementation of learning in the educator aspect in the first cycle was 64.28, in the first cycle the second meeting was 67.8% and in the second cycle it was 75%. The implementation of learning in the aspect of students in the first cycle was 64.2%, in the first cycle the second meeting was 67.8% and in the second cycle was 78.57%. Based on these results, it was concluded that the Problem based learning (PBL) model assisted by video media could improve the integrated thematic learning process in class IV at SDN 39 Pasar Gompong, Pesisir Selatan Regency. an average of 61.65, b) In the first cycle of the second meeting, the average score was 63.75 and c) in the second cycle of the first meeting, the average score was 89.5.